2011
DOI: 10.1074/jbc.m110.215707
|View full text |Cite
|
Sign up to set email alerts
|

The Human Adenocarcinoma-associated Gene, AGR2, Induces Expression of Amphiregulin through Hippo Pathway Co-activator YAP1 Activation

Abstract: Anterior Gradient Homolog 2 (AGR2) is expressed by the normal intestine and by most human adenocarcinomas, including those derived from the esophagus, pancreas, lung, breast, ovary, and prostate. Xenografts of human adenocarcinoma cell lines in nude mice previously demonstrated that AGR2 supports tumor growth. In addition, AGR2 is able to induce in vitro a transformed phenotype in fibroblast and epithelial cell lines. The mechanism underlying the growth promoting effects of AGR2 is unknown. The present study s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
95
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 82 publications
(102 citation statements)
references
References 49 publications
6
95
1
Order By: Relevance
“…Because a definitive marker for stem cells in the gastric corpus has yet to be identified, the hypothesis is inferred from previous studies that have impli- The results concerning cell proliferation may be viewed as contrary to previously published data in which Agr2 enhanced the growth and cell division of adenocarcinoma cell lines. Previous work demonstrated that Agr2 expression activates the Hippo and EGF signaling pathways in lung and esophageal adenocarcinoma cell lines (28). These results may be reconciled if there are different stimuli for cell division among stem cells and progenitors.…”
Section: Agr2mentioning
confidence: 55%
See 1 more Smart Citation
“…Because a definitive marker for stem cells in the gastric corpus has yet to be identified, the hypothesis is inferred from previous studies that have impli- The results concerning cell proliferation may be viewed as contrary to previously published data in which Agr2 enhanced the growth and cell division of adenocarcinoma cell lines. Previous work demonstrated that Agr2 expression activates the Hippo and EGF signaling pathways in lung and esophageal adenocarcinoma cell lines (28). These results may be reconciled if there are different stimuli for cell division among stem cells and progenitors.…”
Section: Agr2mentioning
confidence: 55%
“…Several studies have also demonstrated that Agr2 supports many of the transformed properties of adenocarcinoma cell lines (26,27). Potential mechanisms include activation of the Hippo signaling pathway through the co-activator Yap1 and the induced expression of the EGF receptor ligand amphiregulin (28). The present study explored the in vivo function of Agr2 by generating a null mouse.…”
mentioning
confidence: 99%
“…HQ676606). The activity of human AGR2 protein on lung adenocarcinoma cells in culture depends on stimulation of amphiregulin expression by activation of the Hippo signaling pathway coactivator YAP1 (33). When the axons regenerate after amputation of the newt limb, the nAG protein is up-regulated first in the Schwann cells of the distal nerve sheath and then in gland cells underlying the wound epidermis (26).…”
mentioning
confidence: 99%
“…AGR2 expression in esophageal and lung adenocarcinoma cells induces expression of the EGF receptor ligand amphiregulin (AREG), which is responsible for the transformed phenotype observed in cultured cells in vitro (21). In addition, AGR2 stimulation of AREG expression required activation of the Hippo signaling pathway co-activator, YAP1.…”
mentioning
confidence: 99%